2016
DOI: 10.1007/s11042-016-3426-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive robust video broadcast via satellite

Abstract: Abstract:With increasing demand for multimedia content over channels with limited bandwidth and heavy packet losses, higher coding efficiency and stronger error resiliency is required more than ever before. Both the coding efficiency and error resiliency are two opposing processes that require appropriate balancing. On the source encoding side the video encoder H.264/AVC can provide higher compression with strong error resiliency, while on the channel error correction coding side the raptor code has proven its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Altaf et al implemented the video bit rate switching algorithm in the OpenFlow network, using the OpenFlow network to be able to pass through the network controller, and obtained real-time traffic information of all switch ports. The accuracy and usability of the algorithm are improved, and the interference of other additional data is avoided [ 11 ]. But Mongay Batalla and others found that because when data are transmitted over the network, the network bandwidth will fluctuate greatly and only make bit rate decisions based on the throughput of the network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Altaf et al implemented the video bit rate switching algorithm in the OpenFlow network, using the OpenFlow network to be able to pass through the network controller, and obtained real-time traffic information of all switch ports. The accuracy and usability of the algorithm are improved, and the interference of other additional data is avoided [ 11 ]. But Mongay Batalla and others found that because when data are transmitted over the network, the network bandwidth will fluctuate greatly and only make bit rate decisions based on the throughput of the network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several families of nVoD broadcast-oriented protocols such as periodic broadcast [6]- [9], patching [10]- [12], and bandwidth skimming [13]- [15]. All of them split media files into segments and simultaneously broadcast them at different rates according to their relative position in the media file and the initial content playback delay.…”
Section: Introductionmentioning
confidence: 99%